2018
DOI: 10.21082/jbio.v12n2.2016.p81-90
|View full text |Cite
|
Sign up to set email alerts
|

Kekerabatan Beberapa Aksesi Padi Lokal Tahan Hama Penyakit Berdasarkan Analisis Polimorfisme Marka SSR

Abstract: The level of phylogeny among local rice that has identified the resistances to plant pests and diseases needs to be studied to determine the genetic distance, so that information can be used for a recommendation parental crosses. Simple sequence repeat (SSR) markers could be used as one tool to know the degree of phylogeny and the genetic distance between genotypes. The aim of this study was to determine phylogenetic tree and the coefficient of genetic distance of several local rice resistant to host and pest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The GBSS enzyme plays a role in catalyzing the formation of amylose. DNA analysis of the waxy gene allele using the RM190 marker showed that the gene allele is polymorphic [30]. Likewise, the Wx marker was closely related to the waxy gene, which controls the expression of amylose traits.…”
Section: Analysis Of Molecular Markers Associated With Amylose Traits...mentioning
confidence: 99%
“…The GBSS enzyme plays a role in catalyzing the formation of amylose. DNA analysis of the waxy gene allele using the RM190 marker showed that the gene allele is polymorphic [30]. Likewise, the Wx marker was closely related to the waxy gene, which controls the expression of amylose traits.…”
Section: Analysis Of Molecular Markers Associated With Amylose Traits...mentioning
confidence: 99%
“…For analyzing the genetic diversity of pines, the average PIC value of 0.44 where this results in hal 7 primers is instructive. A high PIC value indicates that the primer can detect a significant number of alleles [11]. The informative value of a primer is determined according to [12], which states that a primary is classified as informative if its PIC is less than 0.3.…”
Section: Genetic Diversity Analysismentioning
confidence: 99%